Association of FSHR gene polymorphisms with endometriosis in women visiting tertiary-care hospitals of Lahore, Pakistan - Irfana Liaqat; Najiya al Arifa; Saba Asif; Khalid Parvaiz Lone (Journal of the Pakistan Medical Association, 2021)
Objectives: The study was aimed to explore the association of endometriosis risk factors with single nucleotide polymorphisms rs6166 and rs6165 (Asn680Ser and Ala307Thr) of follicle stimulating hormone receptor (FSHR) gene in Pakistani women. Methods: This study was conducted from 2013 to 2016. The sampling and extraction of DNA was done in Department of Zoology GC University Lahore while the sequencing was performed at Yale University USA. This case control study consists of 364 subjects including 156 women diagnosed with endometriosis and 208 randomly recruited controls. Subjects diagnosed at stage II-IV endometriosis with infertility were pooled for study. The women with adenomyosis, ovarian cancer and leiomyoma were excluded. The whole blood leukocytes were used for DNA extraction. Two important polymorphisms of exon 10 of FSHR gene were analyzed by direct DNA sequencing both in endometriosis and controls. Results: SNP rs6166 in the affected endometriosis subjects exhibited high incidence of allele “A” (Asn/Asn) 68.3% as compared to controls 33.7% (OR= 4.240; P =0.001). Similarly, the allele “A” of SNP rs6165 (Thr/Thr) was more frequent in endometriosis 67.3% than in control subjects 37.5% (OR =3.430, P =0.001). The occurrence of haplotype AA (Asn/Thr) was 45.5% in endometriosis and 11 % in control subjects (P= 0.001). Remarkably, the incidence of haplotype GG (Ser/Ala) was contrary to previous observations, since only 9.9% occurred in endometriosis as opposed to 45.2% in controls (P= 0.001). Continuous...